Development of integrative thematic environment-based learning materials - Wijanarko, Tiok (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
This study aimed to develop integrative thematic learning materials based on the surrounding environment and evaluate their effectiveness in improving students' environmental awareness and learning autonomy. Utilizing the Borg & Gall development model, the research followed a systematic process including interviews, observations, and surveys. Validation by curriculum and subject matter experts rated the developed materials as highly suitable. The materials were implemented and assessed through limited and operational trials with elementary school students. Findings indicated significant improvements in both environmental awareness and learning autonomy, supported by paired sample t-test results showing a significance level of 0.000. Key components of the developed materials included contextually relevant syllabi, lesson plans, instructional content, and student worksheets that integrated the surrounding environment as a learning medium. These materials facilitated experiential learning, encouraging direct interaction with real-world environmental challenges. This approach not only fostered positive attitudes toward environmental care but also promoted independent learning, enhancing students' ability to manage and evaluate their own learning processes. Keywords: thematic learning, environmental integration, environmental awareness, learning autonomy, instructional materials development